Juridical Review of The Regulation of Criminal Acts Against Child Abuse Accompanied by Acts of Violence - Atika Windynata Sipayung; Henry Aspan (International Journal of Society and Law, 2024)
Child protection is a very important issue because children are the next generation of the nation and the implementers of future development. In Indonesia, child protection aims to ensure children's rights to live, grow, and develop optimally in accordance with human dignity. However, despite increased protection efforts, cases of crimes against children, such as molestation accompanied by violence, have also increased. These crimes have a significant impact on victims, violate human rights, and damage children's dignity and mental health. The Indonesian government has passed Law No. 35 of 2014 concerning Child Protection to provide legal clarity and legal certainty in handling cases of child molestation. This law includes the process of investigation, prosecution, and examination in court. The main issue discussed was how criminal liability for the perpetrators of molestation of minors was accompanied by violence, as well as the basis for the judge's consideration in the case, especially in the study of decision number 83/Pid.sus/2021/PN Sgl.